Fullstack Implementation Using Angular Framework and Springboot in the Participant Admission Information System New Education (PPDB): RA DAARUN Case Study - NISAA - Alifia Khaerunnisa; Dadi Rosadi; Haris Supriatna; Dadang Latif (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
RA DAARUN-NISAA is an educational institution situated in a specific area in Bandung. It annually admits new students. This university attracts many fans due to its engaging learning system that prevents students from feeling bored and its rigorous teaching system. Nevertheless, the admission process at RA DAARUN-NISA is still carried out manually. Due to the absence of a student admission data management system, the incoming data has yet to be integrated into the system. Since the student admission process has yet to be digitized, there are still instances of duplicate data. Consequently, the operator must manually organize the data before inputting it into the central system. A design for an information system to accommodate new students was developed based on the issues identified in the research findings. The research methodology employed in this thesis is the descriptive analysis method. The system development method employed is the SDLC (Software et al.) method, which utilizes a waterfall model. The system was designed utilizing the Angular framework for the front end and Springboot for the back end, with PostgreSQL as the database. The research concludes that an information system has been developed at RA DAARUN-NISAA to facilitate the registration process for new students. This system allows prospective students to register more efficiently while enabling direct management and minimization of data during the registration process. the duplicate. Recommendations for researching student admission information systems involve creating and maintaining a system that operates efficiently and at its highest potential.